VERIFICATION AND INTERPRETATION OF THE I-XE CHRONOMETER - ABSOLUTE I-XE AGES OF INDIVIDUAL PHOSPHATE GRAINS AND THE BJURBOLE STANDARD - Brazzle R.H.; Pravdivtseva O.V.; Meshik A.P.; Hohenberg C.M. (My University, 1999)
Comparisons of I-Xe and Pb-Pb relative ages are made for phosphate and feldspar separates from 12 different meteorites. In all cases where I-Xe ages can be measured in phosphate, I-Xe and Pb-Pb chronometers agree within experimental uncertainty. No discordant phosphate samples are observed. With the exception of Allegan, I-Xe ages for feldspar separates generally agree with Pb-Pb ages for the corresponding phosphate. The general concordancy observed between I-Xe and Pb-Pb chronometers suggests that the I-Xe system is a reliable and interpretable chronometer when applied to single minerals systems. Allegan feldspar differs from the other feldspar separates, predating its phosphate by ~17 Ma, with an I-Xe age indistinguishable from those of Orgueil and Murchison magnetites, among the oldest observed.